Detection of defect in concrete using elastic wave tomography reconstruction technique / Liu Kit Fook - Liu, Kit Fook (2017)
Non-destructive evaluation (NDE) and structural health monitoring (SHM) methods have become a vital technology in civil engineering industry. Defects found in new or aging structures may cause casualty. Hence, detection and assessment of defects in structures have to be carried out effectively. The tomography technique is one of the NDE methods that evaluate soundness of concrete structures by providing visualization to its interior. In this study, three different types of elastic wave properties have been considered in developing tomography reconstruction methodologies namely travel time (velocity), amplitude and frequency. The developments of algorithms for these methodologies are undertaken, which are fundamentally based on ray-tracing approach and SIRT. To verify effectiveness of the methodologies, numerical simulations of wave motion and experimental works were conducted for concrete with honeycomb defect, surface deterioration and partially grouted tendon duct. In this study, it was found that the travel time tomography was less sensitive than the amplitude tomography and frequency tomography in visualizing defect. However, with the use of Q-value as observed data in tomography reconstruction, visualization accuracy has improved substantially. The interpretation of results becomes more accurate by assessing and comparing tomography reconstructions of the three wave parameters. Following that, a new implementation procedure for tomography technique utilizing the proposed wave parameters is recommended to optimize instrumentation and signal processing potentially for reliable in-situ assessment purposes.